Spontaneous closure of coronary artery fistula. Issue 4 (October 1984) - Hackett, D; Hallidie-Smith, K A
Abstract : A coronary artery fistula diagnosed in a 1 year old girl closed spontaneously during childhood. This outcome has been documented in only three previous cases.